Consumo de frutas no município de Upanema – RN - Costa, Rodolfo Emanuel da Silva (Universidade Federal Rural do Semi-Árido, 2020)
The knowledge of consumption and aspects of fruit quality in the perception of consumers is of paramount importance for the availability of products with better quality and especially to meet the requirements of consumers. In view of this, this study aimed to assess the frequency of fruit consumption and the perception of consumers regarding the quality requirements of the municipality of Upanema in the state of Rio Grande do Norte. For this purpose, a questionnaire was designed to interview consumers who were specially destined to buy fruits at the free markets in the municipality. One hundred interviews were conducted, in which the participants answered questions such as: name; sex; age group; education, monthly income; fruit consumption; how often fruit was consumed, whether it was daily, weekly or monthly; species of fruit consumed and in which range of consumption and what quality requirements are adopted in the choice and purchase of fruit. There were few varieties of fruit consumed in this municipality, with bananas being the most consumed fruit. Consumers in the municipality of Upanema consider that the appearance of the fruit and the price are important characteristics and determine the choice of fruit when purchasing or not the product. The frequency of fruit consumption is considered low, and it is important to raise awareness to increase the frequency and variety of fruits in the diet of the local population.
Monografia
Keywords: Fruta; Consumidor; Consumo; Qualidade; Fruit; Consumer; Consumption; Quality; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA